Analysis of Metal Copper Concentration at Candy using Atomic Absorption Spectrophotometry (AAS) - Rahmawati, Eny; Dewi, Diana Candra; Fasya, Ahmad Ghanaim; Fauziyah, Begum (ALCHEMY, 2015)
Candy sold in the market could be containing a heavy metals like copper. In this study, candy was destructed with HNO3, HNO3/H2SO4 (3:1) dan HNO3/H2SO4/H2O2 (6:2:1) to know the best matter oxidixer for copper. Then, evaluated the levels of copper using Atomic Absorption Spectrophotometer (AAS). The one way anove result with F test showed that the best oxidizer for copper in candy is HNO3/H2SO4. The average concentration of Copper in candy coded A, B, C, D, and E were 1. 72 mg/Kg; 1.69 mg/Kg; 1.57 mg/Kg; 1.71 mg/Kg; and 1.69 mg/Kg respectively. The content of copper in candies were the under daily dietary recommended limit based on SNI regulation.Â Key Words: Atomic Absorption Spectrophotometry, candy, matter oxidizer, time stability, wet destructionÂ